Study on the multiple cyclization reactions and the formed structures in poly(acrylonitrile‐co‐itaconic acid) copolymers during thermal treatment. (2nd March 2017) - Fu, Zhongyu; Liu, Baijun; Sun, Lihao; Deng, Yunjiao; Zhang, Huixuan
Abstract : The present work provided some in‐depth understanding on the role of itaconic acid (IA) in the structural evolution of poly(acrylonitrile‐co‐itaconic acid) (PAI) polymers and the formed cyclic structures during thermal treatment. As the increasing content of IA, the cyclization initiated by the ionic mechanism increased with the less β‐amino nitrile formed and the higher extent of cyclization. The IA comonomer initiated multiple cyclization reactions, namely, the first ionic cyclization and the second ionic cyclization, by the jump transportation of activation species between different PAI chains during thermal treatment. The times of the jump transportation of activation species was about two or three at 250°C. The presence of IA comonomer promoted the formation of long sequence cyclic structures rather than isolated cyclic structure under non‐oxidative condition. The thermal stability of PAI was improved by the more and better cyclic structures and the crosslinking structures caused by the jump transportation of activation species, which reasonably resulted in a better graphitic lattice during the carbonization. Copyright © 2017 John Wiley & Sons, Ltd.